Microbiota fúngica e aflatoxinas em alimentos destinados a cabras - Coelho, Poliana de Oliveira (2010)
Aflatoxins are hepatotoxic, immunosuppressive, mutagenic, carcinogenic and teratogenic metabolites produced by Aspergillus flavus and Aspergillus parasiticus. They are found in various kinds of food, especially grains, and are widely used in the manufacture of animal feed. Aflatoxin B1 has the highest toxic power, and its most important metabolite, aflatoxin M1, is eliminated mainly via the milk. The limit values of aflatoxin accepted by Brazilian legislation are 50 ppb for animal feed, and 0.5 µg/L and 5.0 µg/L, for liquid and powdered milk, respectively. Young people are great milk consumers, and thereby milk toxicity becomes an important public health issue. This study evaluated the fungal microbiota and incidence of aflatoxin M1 in the milk of goats raised in three farms, located in the south of Minas Gerais and Mogiana Paulista region. The culture medium Rose-Bengal Sabouraud agar was used to evaluate food fungal microbiota. The presence of aflatoxin B1 was assessed by thin layer chromatography. Aflatoxin M1 in milk was determined by immunoaffinity column cleanout with high performance liquid chromatography (HPLC). In addition, meteorological conditions were surveyed in the regions studied to measure the pluviometric index, the average temperature and relative humidity of air, where the periods of higher incidence of fungi and toxins were found in feed and milk. Two feed samples were collected: concentrate and fodder, with four replications, in two different seasons (rains and drought). Milk samples were also collected, with four replications. Two experiments were conducted: one in the rainy season; another in drought. Their statistical design was completely randomized and factorial . The Tukey test was applied at the 5% significance level. The results showed that the improved methods were efficient to detect aflatoxin: thin layer chromatography, in feed; and high performance liquid chromatography, in milk. The good quality of the goat milk was confirmed by the absence of aflatoxin in the samples. However, the qualitative analysis of Aspergillus cultures revealed that of the 64 samples analyzed, 22,6% were contaminated by aflatoxin B1.